Comparison of the efficacy of three PubMed search filters in finding randomized controlled trials to answer clinical questions. Issue 5 (16th September 2010) - Yousefi‐Nooraie, Reza; Irani, Shirin; Mortaz‐Hedjri, Soroush; Shakiba, Behnam
Abstract: Objective The aim of this study was to compare the performance of three search methods in the retrieval of relevant clinical trials from PubMed to answer specific clinical questions. Methods Included studies of a sample of 100 Cochrane reviews which recorded in PubMed were considered as the reference standard. The search queries were formulated based on the systematic review titles. Precision, recall and number of retrieved records for limiting the results to clinical trial publication type, and using sensitive and specific clinical queries filters were compared. The number of keywords, presence of specific names of intervention and syndrome in the search keywords were used in a model to predict the recalls and precisions. Results The Clinical queries‐sensitive search strategy retrieved the largest number of records (33) and had the highest recall (41.6%) and lowest precision (4.8%). The presence of specific intervention name was the only significant predictor of all recalls and precisions ( P = 0.016). Conclusion The recall and precision of combination of simple clinical search queries and methodological search filters to find clinical trials in various subjects were considerably low. The limit field strategy yielded in higher precision and fewer retrieved records and approximately similar recall, compared with the clinical queries‐sensitive strategy. Presence of specific intervention name in the search keywords increased both recall and precision.